India’s preparedness for zero hunger - Mohapatra, T.; Arunachalam, A.; Jha, S. K. (Indian Farming, 2018)
India has addressed the legislative and administrative, agricultural R&D, targeted public distribution system, trade policies and all other issues to ensure food and nutritional security of its over 1.3 billion people and doing its bid whole-heartedly and is also ready to respond very earnestly to FAO’s call for Zero Hunger by 2030. To achieve this impeccable target, it is time we necessitate new strategies to reduce malnutrition by bringing changes in food systems. Novel ideas such as nutri-gardens, nutri-farms and nutri-smart village concepts should be piloted for upscaling and outscaling apart from achieving climate resilience and sustainability in food production through diversified agriculture per se. Further, policy re-alignments and covergence of government programs shall fortify better efficacy of program outputs, and be linked to the One Health Program of the Government of India.